PENGARUH STRATEGI SURVEY, QUESTION, READ, RECITE, REVIEW (SQ3R) BERBANTUAN MEDIA KOMIK DIGITAL TERHADAP PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN PESERTA DIDIK DI SEKOLAH DASAR - Setianingsih, Desti; Nurmahanani, Indah; Tiara Antik Sari, Nadia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Reading comprehension is an important skill that every student must have. Reading is one of the most difficult and challenging learning activities, therefore many students find reading difficult. This study is motivated by the low reading ability of elementary school students which is indicated by the low motivation of students to read. This study aims to find out: 1) the improvement of students' reading skills before and after using the SQ3R learning strategy with the help of digital comic media; 2) the effect of the SQ3R strategy using digital comic media on improving the reading skills of elementary school students. The type of research used is quantitative research with a one group pretest posttest design. The sample of this study amounted to 24 students consisting of grade VB students studying in SDS IT Cendekia. Based on the results of the study, it was concluded that: 1) there is an increase in students' reading skills before and after the application of the SQ3R learning strategy using digital comic media; 2) the effect of the SQ3R strategy supported by digital comic media on grade VB reading comprehension. The reported impact is 36.2% and the rest is determined by other variables.   Keywords: digital comics media, reading comprehension ability, SQ3R strategy